Pengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pada Pt. Catur Mitra Sejati Sentosa - Cetrin Salsa Dilla; M. Azis Firdaus; Widhi Ariyo Bimo (Jurnal Ekonomi dan Bisnis Digital, 2024)
The purpose of this study is to determine the influence of the work environment and work stress on employee performance at PT. Catur Mitra Sejati Sentosa (Mitra10 Bogor branch). The population in this study is 241 employees. This study uses the Probability Sampling technique, namely Proportionate Stratified Random Sampling using the Slovin formula, where from all employees of Mitra10 Bogor branch who are entitled to be used as a sample, namely 150 employees. This study uses a quantitative method with a data collection technique using a questionnaire containing a number of questions with Likert scale measurements and then tested using validity and reliability tests. The data analysis techniques used were classical assumption test, linear regression analysis, correlation analysis, determination coefficient, t-test and f-test. The results of the study show that the work environment variable has a significant effect on employee performance variables. The variable of work stress has a significant effect on the variable of employee performance. Work environment variables and work stress have a significant effect on employee performance variables.